TWO NEW SPECIES OF Syagrus MART.(ARECACEAE) FROM BRAZIL - Soares, Kelen Pureza (2013)
http://dx.doi.org/10.5902/1980509810553Two new species of Syagrus Mart. (Arecaceae) from Brazil are described and illustrated in this article: the first one, Syagruspompeoi K.Soares& R. Pimenta, a species related to Syagrusprocumbens Noblick&Lorenzi, from which it differs by having a caespitose habit, by the greater length of therachisof leaves (33-50 cm), more pinnaeon each side (8-15), leaflet almost membranaceous with many transverse ribs visible ,as well as longer inflorescence peduncle (10 to 18 cm). The second one, Syagrussantosii K.Soares& C.A.Guim., related to Syagrusschyzophylla (Mart.) Becc., from which it differs by having a larger fruit (2.9 to 4.6 x2.6 to 3.8cm), with the epicarp and the mesocarp usually split at the apex when ripe, bigger endocarp (2.7 to 4.2 x2.4 to 3cm) with homogeneous endosperm, greater amount of pinnae on each side of the leaf and larger pistillate flowers.